Idetification of transcription factor genes and their correlation with the high diversity of Stramenopiles (2012)
The biological diversity among Stramenopiles is striking; they range from large multicellular seaweeds to tiny unicellular species, they embrace many ecologically important algal (e.g., diatoms, brown algae), and heterotrophic (e.g., oomycetes) groups. Transcription factors (TFs) and transcription regulators (TRs) regulate spatial and temporal gene expression. A plethora of transcriptional regulatory proteins have been identified and classified into families on the basis of sequence similarity.The purpose of this work is to identify the TF and TR complement on diverse species belonging to Stramenopiles in order to understand how these regulators may contribute to the observed diversity.